Bridging Cultures through the Introduction of Indonesian Culture in Andong, South Korea - Adzkiya Naila El Azis; Endang Zakaria; Mutiarani; Siti Shofiyah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
This international community service activity aimed to introduce Indonesian culture to international students and local communities in Andong, South Korea. The program was implemented through a direct cultural exchange approach emphasizing interpersonal interaction, discussion, and intercultural communication. The methods used included community education through cultural exchange sessions, participatory observation, and informal communication in public spaces. The results showed that the use of cultural symbols such as batik and tapis effectively increased participants’ interest and understanding of Indonesian cultural diversity. Furthermore, two-way interactions fostered intercultural understanding and enhanced participants’ cultural sensitivity. The activity also contributed to improving the implementer’s intercultural communication skills. Therefore, this program demonstrates that simple, interaction-based approaches can serve as effective strategies in cultural diplomacy and international community service.